2021
DOI: 10.3892/ol.2021.12538
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasin expression is associated with survival in patients with human papillomavirus-positive base of tongue squamous cell carcinoma

Abstract: Patients with human papillomavirus-positive (HPV+) base of tongue squamous cell carcinomas (BOTSCC) have an improved survival compared with patients with HPV-negative BOTSCC and it has been suggested that treatment should be tailored. Before individualized treatment can be introduced, additional prognostic markers are required. A prognostic role of psoriasin has previously been demonstrated outside BOTSCC. Therefore, the present study aimed to examine psoriasin in BOTSCC, with focus on HPV+ BOTSCC, in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Immunological and stem cell markers have been examined extensively, and are still being examined, by IHC and by other means in HPV + and HPV − OPSCC, TSCC, and BOTSCC [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 48 , 50 ]. Moreover, recently, an extensive review on the OPSCC tumor microenvironment with regard to options for immunotherapy presented a detailed overview of immune cells present in the microenvironment and their potential role in the promotion of active or suppressive immune responses in OPSCC [ 90 ].…”
Section: The Search Of Prognostic or Targetable Biomarkers In Hpv + And Hpv − Tscc Botscc And Opsccmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunological and stem cell markers have been examined extensively, and are still being examined, by IHC and by other means in HPV + and HPV − OPSCC, TSCC, and BOTSCC [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 48 , 50 ]. Moreover, recently, an extensive review on the OPSCC tumor microenvironment with regard to options for immunotherapy presented a detailed overview of immune cells present in the microenvironment and their potential role in the promotion of active or suppressive immune responses in OPSCC [ 90 ].…”
Section: The Search Of Prognostic or Targetable Biomarkers In Hpv + And Hpv − Tscc Botscc And Opsccmentioning
confidence: 99%
“…Early on, it was shown that having low CD44 intensity expression or CD98 expression was correlated with better survival irrespective of the HPV status in the tumors, while for tumor suppressor genes LRIG1-3 , only high LRIG1 expression was correlated with a better clinical outcome [ 33 , 34 , 42 ]. More recently, having low psoriasin expression was correlated with better survival in HPV + BOTSCC [ 50 ].…”
Section: The Search Of Prognostic or Targetable Biomarkers In Hpv + And Hpv − Tscc Botscc And Opsccmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve patient stratification and individual tailoring of therapy, efforts have been made to uncover novel prognostic markers in HPV + TSCC/BOTSCC/OPSCC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Stage, age, HPV16 E2 mRNA expression, high CD8 + tumour infiltrating lymphocyte (TIL) counts, and many other molecular markers have been proposed as predictive of prognosis, and models combining multiple markers have been shown to identify 20–56% of all patients with a >95% probability of 3-year disease-free survival [ 15 , 17 , 19 , 20 , 22 , 26 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. However, more biomarkers are required to improve these models and accurately identify a larger proportion of patients with a likely excellent prognosis so that these can receive de-escalated treatments.…”
Section: Introductionmentioning
confidence: 99%